Form and functioning: contextualising the start of the Global Financing Facility policy processes in Burkina Faso - Joël Arthur Kiendrébéogo; Orokia Sory; Issa Kaboré; Yamba Kafando; Meghan Bruce Kumar; Asha S. George (Taylor & Francis Group, 2024)
Background Burkina Faso joined the Global Financing Facility for Women, Children and Adolescents (GFF) in 2017 to address persistent gaps in funding for reproductive, maternal, newborn, child, and adolescent health and nutrition (RMNCAH-N). Few empirical papers deal with how global funding mechanisms, and specifically GFF, support resource mobilisation for health nationally. Objective This study describes the policy processes of developing the GFF planning documents (the Investment Case and Project Appraisal Document) in Burkina Faso. Methods We conducted an exploratory qualitative policy analysis. Data collection included document review (N = 74) and in-depth semi-structured interviews (N = 23). Data were analysed based on the components of the health policy triangle. Results There was strong national political support to RMNCAH-N interventions, and the process of drawing up the investment case (IC) and the project appraisal document was inclusive and multi-sectoral. Despite high-level policy commitments, subsequent implementation of the World Bank project, including the GFF contribution, was perceived by respondents as challenging, even after the project restructuring process occurred. These challenges were due to ongoing policy fragmentation for RMNCAH-N, navigation of differing procedures and perspectives between stakeholders in the setting up of the work, overcoming misunderstandings about the nature of the GFF, and weak institutional anchoring of the IC. Insecurity and political instability also contributed to observed delays and difficulties in implementing the commitments agreed upon. To tackle these issues, transformational and distributive leaderships should be promoted and made effective. Conclusions Few studies have examined national policy processes linked to the GFF or other global health initiatives. This kind of research is needed to better understand the range of challenges in aligning donor and national priorities encountered across diverse health systems contexts. This study may stimulate others to ensure that the GFF and other global health initiatives respond to local needs and policy environments for better implementation.